An Outcome-Centered Comparative Analysis of Counter-Human Trafficking Coalitions in the Global South. (August 2021) - Foot, Kirsten; Sworn, Helen; Alejano-Steele, AnnJanette
A recurring set of questions in the multidisciplinary literature on interorganizational collaboration concerns the relationships between collaboration structures, processes, activities, and outcomes for the coalition as well the societal problem(s) the coalition seeks to address. These questions apply to counter-human trafficking coalitions as well. This mixed-method study helps address several gaps in extant scholarship via a comparative analysis of three nationally-scoped, counter-human trafficking coalitions comprised of nonprofit organizations operating in Global South countries. The key finding is that constructive leadership practices explain positive outcomes in ways that structures and activities do not. Implications are articulated for coalition leaders.